HbA1C as a marker of retrograde glycaemic control in diabetes patient with co‐existed beta‐thalassaemia: A case report and a literature review. (17th November 2019) - Gluvic, Zoran; Obradovic, Milan; Lackovic, Milena; Samardzic, Vladimir; Tica Jevtic, Jelena; Essack, Magbubah; Bajic, Vladimir B.; Isenovic, Esma R.
Abstract: What is known and objective: The HbA1C marker used in assessing diabetes control quality is not sufficient in diabetes patients with thalassaemia. Case description: A male diabetic patient with thalassaemia was hospitalized due to distal neuropathic pain, right toe trophic ulcer, unacceptable five‐point glycaemic profile and recommended HbA1C value. After simultaneously initiated insulin therapy and management of ulcer by hyperbaric oxygen, the patient showed improved glycaemic control and ulcer healing, which led to the patient's discharge. What is new and conclusion: In thalassaemia and haemoglobinopathies, due to discrepancies in the five‐point glycaemic profile and HbA1C values, it is necessary to measure HbA1C with a different method or to determine HbA1C and fructosamine simultaneously. Abstract : The HbA1C marker used in assessing diabetes control quality is not sufficient in diabetes patients with thalassaemia. In thalassaemia and haemoglobinopathies, due to discrepancies in the five‐point glycaemic profile and HbA1C values, it is necessary to measure HbA1C with a different method or to determine HbA1C and fructosamine simultaneously.